Montelukast attenuates side effects of cisplatin including testicular, spermatological, and hormonal damage in male rats - Beytur, Ali; Ciftci, Osman; Oguz, Fatih; Oguzturk, Hakan; Yilmaz, Fethi (Springer, 2012)
In the current study, the protective effect of montelukast (ML) on cisplatin induced reproductive toxicity in rats was investigated. Twenty-eight rats were equally divided into four groups; first group was kept as control. In the second group, ML was orally administered at the dose of 10 mg/kg/day for 10 days. In the third group, CP was intraperitoneally administered at the dose of 7 mg/kg a single injection, and in fourth group, CP and ML were given together at the same doses. Although CP induced oxidative stress via significant increase in the formation of TBARS, it caused a significant decline in the levels of GSH, CAT, GPx, and SOD in rats. In contrast, ML prevents these effects of CP through cause an increase in GSH, CAT, GPx, and SOD levels and a decrease in formation of TBARS. In addition, sperm motility and serum testosterone levels significantly decrease and histopathological damage increases with CP treatment. However, the effects of CP on sperm motility, serum testosterone level, oxidative and histopathological changes are eliminated by ML treatment. In conclusion, the current study demonstrated that the reproductive toxicity caused by CP may be prevented by ML treatment. Thus, it was judged that co-administration of ML with CP may be useful to attenuate the negative effects of CP on male reproductive system.
Keywords: Cisplatin; Montelukast; Reproductive toxicity; Testosterone; Oxidative damage; Sperm quality